2016
DOI: 10.1002/sia.6064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high N2flow ratio on the chemical and morphological characteristics of sputtered N-DLC films

Abstract: a Because of their outstanding characteristics, diamond-like carbon (DLC) thin films have been recognized as interesting materials for a variety of applications. For this reason, the effects of the incorporation of different elements on their fundamental properties have been the focus of many studies. In this work, nitrogen-incorporated DLC films were deposited on Si (100) substrates by DC magnetron sputtering of a graphite target under a variable N 2 gas flow rate in CH 4 + N 2 + Ar gas mixtures. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…It is observed that all DLC and DLC(N) films showed acceptable failures, with the classifications HF1, HF2 and HF3 in the evaluation of the adhesion of the film to the metallic substrate 33 , as can be seen in Table 2. As already reported in other studies 19,37 , the incorporation of nitrogen favors the adhesion of DLC films, as nitrogen reduces the residual stresses of the film. However, the data in Figure 3 shows that the incorporation of nitrogen improves the adhesion of the DLC film until the percentage of 30% N 2 , which presented the lowest percentage of delamination compared to the other films.…”
Section: Morphological and Mechanical Characterizationsupporting
confidence: 77%
See 1 more Smart Citation
“…It is observed that all DLC and DLC(N) films showed acceptable failures, with the classifications HF1, HF2 and HF3 in the evaluation of the adhesion of the film to the metallic substrate 33 , as can be seen in Table 2. As already reported in other studies 19,37 , the incorporation of nitrogen favors the adhesion of DLC films, as nitrogen reduces the residual stresses of the film. However, the data in Figure 3 shows that the incorporation of nitrogen improves the adhesion of the DLC film until the percentage of 30% N 2 , which presented the lowest percentage of delamination compared to the other films.…”
Section: Morphological and Mechanical Characterizationsupporting
confidence: 77%
“…The corrosion resistance of the coated samples presented in the last paragraphs correlates quite well with the physical properties reported in this investigation. It is shown that the lower the delamination (Figure 3) and the higher the wear resistance (insert of Figure 4) the better the corrosion resistance of the DLC(N) sample, which can be intrinsically correlated with the adhesion of the coatings to the substrate, enhanced by the introduction of N in the coating composition 19,37 . On the other hand, the correlation between the DLC(N) coatings thicknesses and their corrosion resistance seems to be a little bit more intricated.…”
Section: Eis Behaviormentioning
confidence: 97%
“…For nitrogen content at 50%, the N-DLC films exhibit a different morphology from those observed. It shows a porous surface, which may be due to the formation of amorphous carbon nitride [10]. There is no gap between the film and the substrate from the cross section, indicating that the adhesion is excellent, and the films all have a dense structure.…”
Section: Resultsmentioning
confidence: 99%
“…Paul et al have studied the effect of gold-doped DLC on residual stress using a radiofrequency (RF) capacitively coupled plasma chemical vapor deposition (CCP-CVD) sputtering technique at room temperature [8]. In addition, numerous researchers and groups have synthesized N-DLC thin films using various deposition methods such as microwave surface-wave plasma CVD [9], DC magnetron sputtering [10], electron cyclotron resonanceassisted microwave plasma CVD (ECR-MPCVD) [11], and inductively coupled plasma deposition (ICP) systems [1,12].…”
Section: Introductionmentioning
confidence: 99%
“…The agglomerated structure was also observed by Zhang et al [29], who obtained an DLC:Si structure on monocrystalline silicone (100) with the clusters that were not an effect of the rough surface of polyurethane. Leal et al [30] obtained DLC:N structures on the same substrate and the investigations proved that increasing the concentration of nitrogen in the gas mixture from 40 to 60 vol% caused an increase in the roughness. In our research, the concentrations of nitrogen in the gas mixture were 83 vol% (J_2) and 80 vol.% (J_3).…”
Section: Morphology and Topography Analysesmentioning
confidence: 95%